Effects of microbial agent application on the bacterial community in ginger rhizosphere soil under different planting years - Wang, Qian; Song, Juan; Zhang, Jinlian; Qin, Xiaojuan; Kang, Yihao; Huang, Shilv; Zhou, Shengmao; Chen, Tingsu (Frontiers in Microbiology, 2023)
Ginger is one of the important spice crops in the world. Due to the prevalence of ginger wilt disease and the lack of effective prevention and control methods, the planting area, total production and value have declined sharply, which have become a key factor restricting ginger industry development in China. Understanding the influence of microbial agents on the rhizosphere microbiota of ginger will facilitate developing novel technologies for the prevention and control of ginger wilt disease. In the new planting and continuous cropping ginger fields, using large-root ginger and microbial agents, two inoculation levels (inoculation and no inoculation) were designed, and high-throughput sequencing technology was used to study the bacterial community structure in the rhizosphere soil at mature stage of ginger. The results showed that newly planted ginger showed a significant yield advantage over continuous cropping ginger, with a yield increase of 39% to 56%, and the lowest ginger wilt disease index. The community structure at the phylum level of soil bacteria in each treatment was very similar to that in the control, but the abundance of some taxonomic units changed significantly. The four dominant phyla of bacteria in mature ginger rhizosphere soil were Proteobacteria, Actinobacteria, Chloroflexi, and Acidobacteria, accounting for 72.91% to 89.09% of the total.The microbial agent treatment of continuous cropping had beneficial microorganisms such as Acidobacteria and Gemmatimonadetes with abundances increased by 12.2% and 17.1%, respectively, compared to the control.The microbial inoculant treatment of newly planted ginger increased the abundance of Acidobacteria and Gemmatimonadetes by 34.4% and 10.7%, respectively,compared to the control.The composition of bacterial communities were affected by changes in soil properties.Redundancy analysis showed that the hydrolysable nitrogen,available phosphorus, available potassium, and organic matter were significantly related to the composition of soil bacterial communities. Therefore, the microbial agents can not only promote the proliferation of beneficial microorganisms in the continuous cropping soil but also further reshape the soil bacterial community structure by changing the soil physicochemical properties such as effective phosphorus. These results provided a reference for related research on the impact of ginger continuous cropping on soil environment and soil management improvement in ginger fields.